Do Exercise and Magnesium Sulfate Improve Infertility Caused by Lithium Carbonate in Male Rats? - Elham Shoghi; Saideh Miri; Fatemeh Maghool; Abbas Ali Niazi; Hamed Fanaei; Parsa Niyazi; Mohadeseh Chahkandi; Abolfazl Parsi-Mood; Hossein Bagheri; Tahereh Safari (Advanced Biomedical Research)
Background: Lithium (Li) is widely used in the treatment of bipolar disorder, but it may lead to toxicity in the reproductive system. Considering the harmful effect of Li consumption on fertility and the positive effect of magnesium sulfate (MgSo4) and moderate-intensity training (MIT) on improving the quality of men’s sperm, the current research was conducted to determine the impact of MIT and MgSo4 on infertility caused by Li. Materials and Methods: Seventy-two male rats were divided into 12 groups, control, Li10 mg/kg/day/ip, MgSo4 80 mg/kg/day/ip; MIT; Li40 mg/kg/day/ip; Li10+MgSo4; Li10+MIT; Li10+MgSo4+MIT; Li40+MgSo4; Li40+MIT; Li40+MgSo4+MIT. All animals received the drugs every day. The groups under the exercise protocol followed this program for 42 days (6 weeks). Total sperm count, sperm concentration, total motility, and progressive motility were analyzed. A blood sample was taken from the heart to quantify testosterone, luteinizing hormone (LH), and follicle-stimulating hormone (FSH). Results: Li40 mg/kg decreased the progressive motility and quantity of sperms together with nonprogressive motility and immobile sperms increased significantly. Administration of MgSo4 and MIT alone and simultaneously led to a significant improvement in the above mentioned parameters. Li40 mg/kg reduced the serum level of testosterone and LH compared to the control group. On the other hand, the administration of MgSo4 and MIT together with Li40 (Li40+MgSo4+MIT) did not have any effect on serum testosterone levels. Conclusions: Li probably causes damage to reproductive functions by affecting the antioxidant system. However, MgSo4 and MIT reduce the impacts of Li on the reproductive system and improved its performance.